2001
DOI: 10.1007/s001070050461
|View full text |Cite
|
Sign up to set email alerts
|

Moisture transport in coated wood. Part 2: Influence of coating type, film thickness, wood species, temperature and moisture gradient on kinetics of sorption and dimensional change

Abstract: The sorption of moisture by spruce and meranti coated with both waterborne and solventborne coatings was studied during controlled conditions. Experimental variables included: coating ®lm thickness, temperature and gradients in relative humidity (33±98, 65±98 or 33±75%), or exposure to liquid water. Changes in moisture content of the wood and the tangential or the radial dimensions were recorded as a function of time. Apparent moisture diffusion coef®cients were calculated from the initial slope of the fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…This condition might have resulted from the reddening due to the formation of chromophore groups in the Eastern beech and the high tendency of the resin within the Scots pine to redden as a result of varnish application. Previously conducted studies report that water borne varnishes has a color changing effect, especially on tanniferous tree species (De Meijer and Militz 2001;Budakçı 2006;Pelit 2007).…”
Section: Value Of the Color Red (+A)mentioning
confidence: 99%
See 2 more Smart Citations
“…This condition might have resulted from the reddening due to the formation of chromophore groups in the Eastern beech and the high tendency of the resin within the Scots pine to redden as a result of varnish application. Previously conducted studies report that water borne varnishes has a color changing effect, especially on tanniferous tree species (De Meijer and Militz 2001;Budakçı 2006;Pelit 2007).…”
Section: Value Of the Color Red (+A)mentioning
confidence: 99%
“…The water that might already be present in the wood body or that might enter the body at a later time plays a significant role in the success of finishing (varnish, coloring, dying) applied on wooden furniture and decorative elements (Wheeler 1983;De Meijer and Militz 2001;De Meijer 2002;Sönmez 2005;Sönmez et al 2009;Sönmez et al 2011). The moisture content of the wooden material, as well as its many other characteristics, is an important aspect that needs to be mastered by the people using wood as the raw material in order to prevent faulty applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] However, it has also been demonstrated that the spatial distribution of water close to the surface is inhomogeneous. [9][10][11][12] Typically, the MC does not reach a steady state but is continuously responding to changes in environmental conditions. 11 Hence, monitoring of the MC with spatial and time resolution is required to properly evaluate the effect of coating on moisture migration.…”
Section: Introductionmentioning
confidence: 99%
“…Coating systems are able to protect wood against moisture ingress and they influence moisture release depending on their permeability for liquid water and water vapour (Wassipaul and Janotta 1972, Janotta 1973, Hora and Böttcher 1995, De Meijer and Militz 2001, Ekstedt 2002, Svane 2004. Moisture conditions in coated panels exposed 45° facing south were investigated by Derbyshire and Miller (1996) by recording wood moisture content with conductivity measurements on a site in the UK.…”
Section: Introductionmentioning
confidence: 99%